Two polymethoxylated flavonoids with antioxidant activities and a rearranged clerodane diterpenoid from the leaf exudates of Microglossa pyrifolia. (March 2015) - Akimanya, Aggrey; Midiwo, Jacob O.; Matasyoh, Joseph; Okanga, Francis; Masila, Veronica M.; Walker, Larry; Tekwani, Babu L.; Muhammad, Ilias; Omosa, Leonidah Kerubo
Graphical abstract: Highlights: Two new flavonoids and one new diterpenoid from Microglossa pyrifolia leaf exudate. Structures elucidated based on spectroscopic evidence. Some flavonoids showed good antioxidant activities. Hydroxyl at C-4′ position in flavones responsible for good antioxidant activities. Oxygenation at C-3 in flavone skeleton responsible for good antioxidant activities. Abstract: Three novel compounds; two polymethoxylated flavonoids, 5, 7, 4′-trihydroxy-3, 8, 3′, 5′-tetramethoxyflavone (1 ), 5, 7, 3′-trihydroxy-3, 8, 4′, 5′-trimethoxyflavone (2 ), and a clerodane diterpenoid; 8-acetoxyisochiliolide lactone (3 ) were characterized from the leaf exudates of Microglossa pyrifolia. In addition, three known polymethoxylated flavonoids including; 5, 7, 4′-trihydroxy-3, 8, 3′-trimethoxyflavone (4 ), 5, 3′4′-trihydroxy-3, 7, 8-trimethoxyflavone (5 ), 5, 3′4′-trihydroxy-7-methoxyflavanone (6 ) and a clerodane diterpenoid; 7, 8-epoxyisocholiolide lactone (7 ) were identified. Their structures were determined on the basis of spectroscopic evidence. All the compounds did not exhibit antiplasmodial and antimicrobial activities at 47.6 μg/mL and were not cytotoxic at 5 μg/mL. Compound6 exhibited modest antileishmanial activity with IC50 value of 13.13 μg/mL with5 and7 showing activities with IC50 values of 31.13 and 38.00 μg/mL, respectively, therefore inactive. The flavonoids (quercetin derivatives, 4 and5 ) showed similar antioxidant activities, using 2, 2-diphenylpicrylhydrazyl (DPPH) assay, with IC50 values of 6.2 ± 0.3 μg/mL for4 (17.3 μM) and5 (17.8 μM) respectively. These activities were comparable to that of the standard quercetin (IC50 value of 6.0 ± 0.2 μg/mL (19.9 μM)), irrespective of methylation of the characteristic hydroxyl groups expected to be responsible for activity and additional substitution at C-8 in ring A of the flavonoid ring. These studies revealed that the presence of an hydroxyl group at C-4′ positions and oxygenation at C-3 in flavone skeleton, appears to be necessary for good antioxidant activities as encountered in compounds1, 4 and5 . Substantial reduction in antioxidant activity was shown by methoxylation of the 4′-OH as observed in compound2 with an IC50 value of 8.79 ± 0.3 μg/mL (24.4 μM).